(3GdGTJbGbs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s ((3CMeO Hf YHO GdbGOQ Hf CMeO Hf ecJhe GdbjSi GdOeTbi s)
(3ChdgG (B:s
(3bjd ddYJHi (B: (3eG HGd GdYQH SejJ CHfGAgG HGdCSeGA GdeSJTfYI hSejJ YHjOgG HGdCSeGA GdeSJMSfI ? dCfgG SejJ CHfGAgG dCYOGFgG , hSejJ YHjOgGdgG s
(3BNQgG (B:s
(3Obje (B: (3GSe , hgh JUZjQ Obe , ef bhdge (B: (3ObeJ aGg ObekG (B: (3EPG cSQJg Je cJGH GdGTJbGb s
(3GdChQGb GdChdi efgG eeRbIs
(3GdfSNI HgG MhGTs
(3HMhGTjgG HYV GdJUMjMGJ hGdJYdjbGJs
(3fSNI fajSI s
(3cJHJ CSeGA GdbHGFd hGdCYdGe HGdMeQI s
(3hbO cJHgG GdYGde GdfGSN dfaSg s
Keywords: (3GddZIs